Immunogenicity and Reactogenicity in Q Fever Vaccine Development - Fratzke, Alycia P.; van Schaik, Erin J.; Samuel, James E. (Frontiers in Immunology, 2022)
Coxiella burnetii is an obligate intracellular bacterium which, in humans, causes the disease Q fever. Although Q fever is most often a mild, self-limiting respiratory disease, it can cause a range of severe syndromes including hepatitis, myocarditis, spontaneous abortion, chronic valvular endocarditis, and Q fever fatigue syndrome. This agent is endemic worldwide, except for New Zealand and Antarctica, transmitted via aerosols, persists in the environment for long periods, and is maintained through persistent infections in domestic livestock. Because of this, elimination of this bacterium is extremely challenging and vaccination is considered the best strategy for prevention of infection in humans. Many vaccines against C. burnetii have been developed, however, only a formalin-inactivated, whole cell vaccine derived from virulent C. burnetii is currently licensed for use in humans. Unfortunately, widespread use of this whole cell vaccine is impaired due to the severity of reactogenic responses associated with it. This reactogenicity continues to be a major barrier to access to preventative vaccines against C. burnetii and the pathogenesis of this remains only partially understood. This review provides an overview of past and current research on C. burnetii vaccines, our knowledge of immunogenicity and reactogenicity in C. burnetii vaccines, and future strategies to improve the safety of vaccines against C. burnetii.